KONSEP PASAR YANG ISLAMI - Adanan Murroh Nasution (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
The market is a mechanism for exchanging natural goods and services and has been going on since the early human civilization. Islam places the market in an important position in the economy. Economic practice at the time of the Messenger of Allah and Khulafaurrasyidin showed the existence of a large market role. The Prophet greatly appreciated the prices formed by the market as a fair price. He rejected any price intervention in the event that price changes occurred due to a fair market mechanism. Markets in Islamic economics require morality, including: fair play, honesty, transparency and justice. If these values have been enforced there is no reason to reject market prices.